TIPOLOGI UMAT ISLAM DI BUMI NGAPAK: TIPOLOGI UMAT ISLAM DI BUMI NGAPAK (Kajian Fenomenologi Umat Islam di Purwokerto) - Saefulloh, Aris; Muhajarah, Kurnia; Macpal, Sunandar (Farabi, 2025)
Purwokerto is known as a city with a distinct cultural identity. Nicknamed the “Ngapak City,” it is characterized by the straightforward and unpretentious dialect of its people, reflecting an open and egalitarian social character. The acculturation between Islam and local culture in this region has given rise to a unique expression of religiosity. Islam did not arrive as a dominating force seeking to replace existing traditions but rather merged harmoniously with long-standing local values. This study aims to explore the dynamics of Islam in Purwokerto using a phenomenological approach to understand religious practices in a deep and holistic manner. The findings reveal that Islam has become an integral part of daily life, evolving through a process of acculturation that fosters diverse yet respectful expressions of faith. At least five typologies of Islamic expression can be identified: Kejawen Islam, Kampung Islam, Sufi Islam (Tarekat), Moderate Islam, and Puritan Islam. This diversity reflects a dynamic and pluralistic face of Islam, yet one that remains harmonious. These typologies represent a contextualized, grounded, and culturally rooted form of Islam in the Ngapak City.